Impact of serum antibodies to HPV serotypes 6, 11, 16, 18 to risks of subsequent genital HPV infections in men: the HIM Study - Pamnani, Shitaldas J. (Cancer Res, 2016)
Naturally induced serum antibodies against HPV may affect risks of subsequent incident genital infections by HPV 6, 11, 16, or 18 in men. In this study, we examined the hypothesis by following 4,123 healthy men every six months(median follow-up time 4.1 years). HPV antibodies were measured at baseline using a virus-like particle-based ELISA assay. Genital HPV genotypes were detected using Roche Linear Array. Incidence proportions and six-month persistence proportions were calculated at six-month intervals. Kaplan-Meier curves and Cox models were used to assess genotype-specific cumulative incidence and hazard ratios (HR), respectively. HPV 6, 11, 16, and 18 seroprevalence was 8.1%, 13.9%, 12.7%, and 10.8%, respectively. Significantly higher rates of incident infections were observed for HPV 16 among baseline seropositive men (adjusted HR 1.37, 95% CI 1.01–1.86), with similar but non-significant HRs for six-month persistent infections. Risk of persistent HPV 18 infection was significantly lower among seropositive men in the unadjusted model (HR 0.22, 95% CI 0.06–0.91), but not in the adjusted model (HR 0.19, 95% CI 0.03–1.37). Incident and six-month persistent infections for HPV 6 and 11 did not differ by baseline serostatus. Baseline serostatus among men was not associated with a reduction in subsequent incident genital HPV 6, 11, and 16 infections. However, protection against persistent HPV 18 infections was observed in unadjusted models. Our research suggests a need of further studies to examine the potentially protective effects of naturally induced HPV18 antibodies in men.